2000
DOI: 10.1088/0953-4075/33/17/102
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Auger spectrum following Kr:2p → 5s photoexcitation

Abstract: Resonant Auger electron spectra following Kr:2p → 5s photoexcitation have been measured for the first time using monochromatized undulator radiation and a cylindrical mirror electron energy analyser. It is found that the kinetic energy of the resonant Auger electron is higher than that of the corresponding normal Auger electron. The angular distribution of the resonant Auger electrons is nearly isotropic relative to the polarization direction of the incident light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…5s state, which is in agreement with previous studies [17,18,23]. The second structure stems from the excitation into the 4d orbital, as seen in the previous data [24].…”
Section: Ion Yield Spectrumsupporting
confidence: 93%
See 1 more Smart Citation
“…5s state, which is in agreement with previous studies [17,18,23]. The second structure stems from the excitation into the 4d orbital, as seen in the previous data [24].…”
Section: Ion Yield Spectrumsupporting
confidence: 93%
“…Normal Auger electron spectra using charged-particle techniques were observed and analyzed, which showed that the 1 G 4 final state yields the strongest peak in the electron kinetic-energy region near 1460 eV [20][21][22]. The resonant Auger transitions were found from the 2p -1 nl states by the present authors, who used monochromatized undulator radiation combined with the grating monochromator having high resolving power [23,24].…”
Section: Introductionmentioning
confidence: 64%
“…The same holds for the Kr L 3 absorption measurements of Schmelz et al (1995). Nagaoka et al (2000) and Okada et al (2005) calibrated their energy scales by referring to the work of Wuilleumier (1971) as is also done here.…”
Section: Photon-energy Calibrationmentioning
confidence: 99%
“…According to the present calculations, the L 1 hole decays by about 90% via these Coster-Kronig processes, which leads to two consequences. First, this leads to a much larger lifetime broadening for the L 1 hole ( (L 1 ) theo = 4.28 eV [37]) as compared to the L 2 ( (L 2 ) theo = 1.31 eV [37]) and L 3 ( (L 3 ) theo = 1.17 eV [37], (L 3 ) exp = 1.152 (20) eV [38]) holes and results in significantly larger widths for the [38] and the N 3 ionization energy [39]. For an alignment to the two-hole binding energy the kinetic energies of the L 2 spectrum [panels (b)] and the L 1 spectrum [panels (c)] are higher by 52.6(1) and 246.3(6) eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to the present calculations, the L 1 hole decays by about 90% via these Coster-Kronig processes, which leads to two consequences. First, this leads to a much larger lifetime broadening for the L 1 hole ( (L 1 ) theo = 4.28 eV[37]) as compared to the L 2 ( (L 2 ) theo = 1.31 eV[37]) and L 3 ( (L 3 ) theo = 1.17 eV[37], (L 3 ) exp = 1.152(20) eV[38]) holes and results in significantly larger widths for the L 1 M 2,3 M 4,5 and L 1 M 4,5 M 4,5 transitions as compared to the L 2 and L 3 Auger decays, and as a consequence to much lower peak intensities. Second,…”
mentioning
confidence: 99%